Creating a Network of Places with Participatory Actions across Cities and Cultures - Madrazo, Leandro; Zupančič, Tadeja; Pak, Burak; Aparício, Maria Irene (The Journal of public space, 2022)
The aim of the A-Place project is to address the problem of placelessness in our multicultural, and interconnected societies from a multidisciplinary and participatory perspective. Artists and creators, educators and students of art and architecture, and cultural agents collaborate with communities in the design and implementation of placemaking activities with the purpose of reinforcing the bonds between people and the places they live in. Activities in locations in several European cities, as well as in digital spaces, have contributed to the creation of a network of places ‒both tangible and intangible ‒ that exploit the multiple dimensions of public space as a stage for leisure, entertainment and education. A sequence of planning, performing, reflecting and evaluating has been applied to the activities carried out in the first year of this four-year project. The outcomes of this first cycle will help to expand the network of places in the coming years of the project. A key issue for the further development of the project is the evaluation of the impact of placemaking activities on the communities.